Cohort for Tuberculosis Research by the Indo-US Medical Partnership (CTRIUMPH): protocol for a multicentric prospective observational study. Issue 2 (25th February 2016) - Gupte, Akshay; Padmapriyadarsini, Chandrasekaran; Mave, Vidya; Kadam, Dileep; Suryavanshi, Nishi; Shivakumar, Shri Vijay Bala Yogendra; Kohli, Rewa; Gupte, Nikhil; Thiruvengadam, Kannan; Kagal, Anju; Meshram, Sushant; Bharadwaj, Renu; et al.
Abstract : Introduction: Tuberculosis disease (TB) remains an important global health threat. An evidence-based response, tailored to local disease epidemiology in high-burden countries, is key to controlling the global TB epidemic. Reliable surrogate biomarkers that predict key active disease and latent TB infection outcomes are vital to advancing clinical research necessary to 'End TB'. Well executed longitudinal studies strengthening local research capacity for addressing TB research priorities and advancing biomarker discovery are urgently needed. Methods and analysis: The Cohort for Tuberculosis Research by the Indo-US Medical Partnership (CTRIUMPH) study conducted in Byramjee Jeejeebhoy Government Medical College (BJGMC), Pune and National Institute for Research in Tuberculosis (NIRT), Chennai, India, will establish and maintain three prospective cohorts: (1) an Active TB Cohort comprising 800 adults with pulmonary TB, 200 adults with extrapulmonary TB and 200 children with TB; (2) a Household Contact Cohort of 3200 adults and children at risk of developing active disease; and (3) a Control Cohort consisting of 300 adults and 200 children with no known exposure to TB. Relevant clinical, sociodemographic and psychosocial data will be collected and a strategic specimen repository established at multiple time points over 24 months of follow-up to measure host and microbial factors associated with (1) TB treatment outcomes; (2) progression from infection to active TB disease; and (3) Mycobacterium tuberculosis transmission among Indian adults and children. We anticipate CTRIUMPH to serve as a research platform necessary to characterise some relevant aspects of the TB epidemic in India, generate evidence to inform local and global TB control strategies and support novel TB biomarker discovery. Ethics and dissemination: This study is approved by the Institutional Review Boards of NIRT, BJGMC and Johns Hopkins University, USA. Study results will be disseminated through peer-reviewed journals and research conferences. Funding: NIH/DBT Indo-US Vaccine Action Programme and the Indian Council of Medical Research.